2021
DOI: 10.3390/molecules26092754
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Halogenated Compounds from Marine Actinomycetes

Abstract: Marine actinomycetes, Streptomyces species, produce a variety of halogenated compounds with diverse structures and a range of biological activities owing to their unique metabolic pathways. These halogenated compounds could be classified as polyketides, alkaloids (nitrogen-containing compounds) and terpenoids. Halogenated compounds from marine actinomycetes possess important biological properties such as antibacterial and anticancer activities. This review reports the sources, chemical structures and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 78 publications
(109 reference statements)
0
17
0
1
Order By: Relevance
“…The genus Streptomyces alone accounts for a remarkable 80% of the actinobacterial natural products and, therefore, has unrivaled biosynthetic capacity in the microbial world ( Manivasagan et al, 2014b ; Hu et al, 2015 ). In particular, marine Streptomyces are known to produce broad-range-active natural products with immunosuppressant, antifungal, anticancer, antiparasitic, or antithrombotic activities ( Ser et al, 2017 ; Wang et al, 2021 ), such as pactamides ( Saha et al, 2017 ) and streptoseomycin ( Zhang et al, 2019 ). Thus, the isolation and characterization of novel marine streptomycetes species are important for identifying new potential bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Streptomyces alone accounts for a remarkable 80% of the actinobacterial natural products and, therefore, has unrivaled biosynthetic capacity in the microbial world ( Manivasagan et al, 2014b ; Hu et al, 2015 ). In particular, marine Streptomyces are known to produce broad-range-active natural products with immunosuppressant, antifungal, anticancer, antiparasitic, or antithrombotic activities ( Ser et al, 2017 ; Wang et al, 2021 ), such as pactamides ( Saha et al, 2017 ) and streptoseomycin ( Zhang et al, 2019 ). Thus, the isolation and characterization of novel marine streptomycetes species are important for identifying new potential bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Such halogenated bis-indole alkaloids display potent cytotoxic or antibacterial activities or both, and they are thus considered promising anti-cancer or antibacterial leads. In the same way, a series of marine-derived chlorinated bis-indoles were shown to inhibit methicillin-resistant S. aureus (MRSA) pyruvate kinase significantly, with their halogenated indole ring being implicated as a critical pharmacophore [ 45 ]; this has been reported by Wang et al [ 177 ] and is well known that marine actinomycetes produce a variety of halogenated compounds with diverse structures and a range of biological activities owing to their unique metabolic pathways [ 31 , 177 ].…”
Section: Discussionmentioning
confidence: 95%
“…Among these were found aromatic polyketides as described by Dong et al, Ahamad et al, and Govindarajan et al [ 61 , 68 , 151 ], angucyclines described by Akhter et al [ 54 ], polyketide–terpenoid as Naphthoquinone, reported by Shen et al [ 37 ], macrolides, described by Braña, Zhang and Wu [ 52 , 67 , 107 , 152 ], etc. Likewise, some chlorinated compounds were frequent, such as chlorinated bis-indole alkaloids and chlorinated 3-phenylpropanoic acid described by Song et al [ 45 ] and Shaala et al [ 124 ]; this may be due to the concentrations of chloride and bromide ions in the ocean [ 177 ]. Interestingly, marine-derived bis-indole compounds typically contain halogen atoms in their structures.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria, in particular, marine streptomyces species generate a diverse range of halogenated compounds with a wide spectrum of biological activities. These compounds possess various chemical structures including polyketides, alkaloids (nitrogen-containing compounds) and terpenoids ( Wang et al, 2021 ). It was reported that halogenated substances from marine actinomycetes have crucial biological activities such as antibacterial and anticancer properties.…”
Section: The Structure–activity Relationship Of Natural Productsmentioning
confidence: 99%